Peran Serta Elit Desa dalam Pengembangan Pariwisata di Desa Cempaga Kecamatan Banjar Kabupaten Buleleng Bali - Diah Andini, Nanda; Pujaastawa, I.B. Gde (Humanis, 2018)
Tourism sector has become driving force in development of Bali area. Even today, tourism is inseparable part of community and development at Bali area. Cempaga Buleleng village because of elite (leaders of community) initiative  is doing tourism development. Tourism development in Cempaga village has give an impact of social cultural, economic, and environment. As for this study aims to know of (a) form of participation elite in tourism development at Cempaga village, (b) impact from tourism development at Cempaga village. Participation elite in tourism development at Cempaga village can be review using a theory from Karl Mannheim, and review about impact of tourism development is using a theory from Dickman. Concept used in this study is about participation, elite, and tourism development. This study used ethnograpic research methods with qualitative research and collecting data from determination of informants, observation, interview, and literature review.The results form of participation elite in tourism development at Cempaga village seen in some activities as like; be allied and collaborate developing tourism with Forum Panca Desa Mahagotra Bali Aga SCTPB, participation at preservation and development of art and culture Cempaga village. Tourism development at Cempaga village involve of positive impact from social cultural are seen in improvement of tourism management. The negative impact from tourism development is traditional art that seen as a commercial resource to attract tourists. The positive impact from the economic perspective are seen in the increase of people's income but also has a negative impact on increasing only at certain moments or seasonally. Positive impacts on the environment are seen in maintaining environmental hygiene by making landfills (TPST). While the negative impact for the environment is from construction of many stalls and house estates.Suggestions from the results of this study on the government is expected to provide adequate facilities and budget for clean water to build facilities and infrastructure supporting tourism, to the tourism industry is expected in the development of tourism at Cempaga village oriented to all levels of society to make income distribution, and to the public are advised to increase active role in the field of tourism so as to improve the welfare.